TEMPERING THE WILL QUALITIES OF JUNIOR SCHOOL AGE STUDENTS IN THE EDUCATIONAL PROCESS - Yuldashev Mamurali Otakoziyevich; Yuldashev Dilshodjon Mamurovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, we analyzed the considerations of tempering the willpower qualities of junior school age students in the educational process. On the basis of the conclusions reached, proposals have been developed.